Structure of Motivation for Training in Engineering Specialties - Grigor Grigorov; Iliyan Lilov (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
This article researches the structure of motivation for training in engineering specialties as well as the satisfaction from it. It analyses the main factors that form students' motivation for training and the interrelationships between them. A comparative analysis of the state of the motivational structure is carried out of the opinions of both lecturers and students in engineering specialties, taking into account the similarities and differences between them. The article identifies the specific factors that form the motivation for the students in the aforementioned specialties, the problems in their training, and gives guidelines for their overcoming in order to improve the quality of training. The results of the research would contribute to raising the interest in training in engineering specialties, attracting and retaining motivated learners, and meeting the growing shortage of engineers on the labour market.
Keywords: I21; 330; motivation; training; engineering specialty